Chemical constituents of the barks of Litsea glutinosa collected in Thai Nguyen province, Vietnam - Ninh, Pham Thi; Luu, Nguyen Thi; Anh, Nguyen The; Loc, Tran Van; Ha Mi, Nguyen Thi; Phuong Thao, Tran Thi; Sung, Tran Van (Vietnam Journal of Chemistry, 2015)
From the ethyl acetate extract of the barks of Litsea glutinosa four compounds including cis-5,8,11,14,17-eicosapentaenoic acid methyl ester (1), spatozoate (2), betasitosterol (3) and daucosterol (4) have been isolated. Compound (5) 1-heptadecanol, compound (6) 1-eicosanol and compound (7) glycerol 1,3-di-(9Z,12Z-octadecadienoate) 2-hexadecanoate were isolated from the n-hexane extract. Their structures were elucidated by the analysis of the IR, MS and NMR spectra. Compounds (1), (2), (5), (6), (7) were isolated for the first time from Litsea glutinosa. Keywords. Litsea glutinosa, cis-5,8,11,14,17-eicosapentaenoic acid methyl ester, spatozoate, betasitosterol, daucosterol, 1-heptadecanol, 1-eicosanol, glycerol 1,3-di-(9Z,12Z-octadecadienoate) 2-hexadecanoate.